2013
DOI: 10.1371/journal.pone.0060472
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NO Synthase Gene Polymorphisms and Risk of Ischemic Stroke in Asian Population: A Meta-Analysis

Abstract: BackgroundThe association between polymorphism 4b/a, T-786C and G894T in endothelial NO synthase gene (eNOS) and ischemic stroke (IS) remains controversial in Asian. A meta-analysis was performed to better clarify the association between eNOS gene and IS risk.MethodsBased on the search of PubMed, Web of Science (ISI), CNKI (National Knowledge Infrastructure), Wan Fang Med Online and CBM (Chinese Biology Medical Literature Database) databases, all eligible case-control or cohort studies were identified. Pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Recently, meta-analyses have reported the significant association between eNOS 4a/b polymorphism and increased risk of ischemic stroke, particularly in Asian population rather than Caucasian population. [34][35][36][37] Lower nitric oxide plasma level was detected among 4a allele carriers than in the 4b wild-type allele. 31 A similar trend found in genotype-phenotype studies on NOS protein concentration and enzyme activity, indicates that protein expression and enzyme activity were lower in 4a4b genotype as compared to 4b4b genotype.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, meta-analyses have reported the significant association between eNOS 4a/b polymorphism and increased risk of ischemic stroke, particularly in Asian population rather than Caucasian population. [34][35][36][37] Lower nitric oxide plasma level was detected among 4a allele carriers than in the 4b wild-type allele. 31 A similar trend found in genotype-phenotype studies on NOS protein concentration and enzyme activity, indicates that protein expression and enzyme activity were lower in 4a4b genotype as compared to 4b4b genotype.…”
Section: Discussionmentioning
confidence: 88%
“…Possible link between NOS3 894G>T and cardiovascular morbidity and mortality has been widely studied, unfortunately, most studies published so far were performed on non-Caucasian populations. Four recent meta-analyses found association of NOS3 SNP with ischemic stroke [30,31,32] or coronary heart disease [33] in Asian populations. No such association was found for Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…According to some metaanalyses, no significant differences exist between the Asian and Caucasian populations in terms of the T786C genotypes and allele distributions (Table 3) [6,10]. However, in a contrasting metaanalysis reported by Wang et al [17], the predominance of the C allele of the T-786C polymorphism was highlighted in Asians, indicating a significant protective effect against the risk of ischemic stroke in the codominant models (C vs T for T-786C) ( Table 3) [17]. In our study, we also observed that the C alleles and TC heterozygote polymorphism genotype were significantly lower in the patient group (with the possibility of a protective effect) in the Anatolian population (Tables 2 and 3).…”
Section: T-786c Polymorphismmentioning
confidence: 95%